(3GdHOhQ GdSGaQI aj Ydhe GdBNQIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3hHYO agPG eG JbOe Hg GdhYO ef NWHI cJGH GdHQRN ef cJGH TGa ai Yde GdBNQI s
(3BNQgG (B:s
(3BNQ GdehLhO (B: (3ajbhd Gddg (B: (3CNQLhG ef GdfGQ ef YQaJe , ajNQL ChdFc MJi dGjHbi CMO efge , Ke jCPf Gddg JYGdi ai GdTaGYI s
(3fSNI bOjeIs
(3YdjgG BKGQ QWhHIs
(3MhGagG eJCcdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B231s
Keywords: (3GdJhMjO hGdedd hGdfMds